The natural numbers in the teaching and learning process of math through the playful / Os números naturais no processo de ensino e aprendizagem da matemática através do lúdico - Édel Alexandre Silva Pontes (Universidade Estadual de Alagoas, 2017)
The goal is to present an activity, in the form of a game that will produce greater cognitive and psychomotor development in our players, our children. The prerequisites required are only the knowledge of natural numbers and the basic rule of potentiation. In today's mathematical teaching it is necessary to construct and develop in our children new techniques that can stimulate the new. And the basis of this construction is based on four pillars: Logical Reasoning, Creativity, Willingness and Will to Learn. The need to make the topics of mathematics be presented from practical models makes this application quite significant and motivating for the understanding of what is the science of life. With this, it is expected that the well-constructed and easily assimilated game allows our students to be able to comply with rules and steps, be ethical, critical and develop their skills in building a school of transformation